Use of Transverse Abdominis block for Post Operative pain management in Patients undergoing Emergency Cesarean Sections : a prospective study: Use of TAP block in Emergency Cesarean sections (Pain medicine, 2024)
INTRODUCTIONPostoperative pain management is an essential aspect of perioperative care for patients undergoing emergency Cesarean sections. Adequate pain control not only improves patient comfort and satisfaction but also facilitates early mobilization, reduces the risk of complications, and shortens hospital stays. Transverse abdominis plane (TAP) block is a well-established technique for providing analgesia to the anterior abdominal wall, which can significantly reduce postoperative pain. In recent years, ultrasound guidance has been increasingly used to improve the accuracy and safety of TAP block. This research article aims to review the use of ultrasound-guided TAP block for postoperative analgesia in patients undergoing emergency Cesarean Sections.Methodology : A total of 60 patients who underwent Emergency Cesarean Sections were included in the study. All received bilateral US-guided TAP blocks with either ropivacaine 0.5% 20 ml on each side i. e. 40 ml total or saline. All participants received a spinal anaesthetic with bupivacaine, followed by postoperative acetaminophen, non-steroidal anti-inflammatory drugs, and patient-controlled i.v. tramadol . Each patient was assessed 24 h after delivery for PCA Tramadol usage, average pain score, nausea, vomiting, itch and duration of hospital stay.Results and Conclusion Out of the total 60 patients , 30 were in the study group and 30 in placebo group. Total PCA Tramadol use in 24 h was reduced in the study group compared with the placebo group ( P
Keywords: TAP block; cesarean section; transverse abdominis plane block; Ropivacaine